Using relevant resources propose a project offering a development marketing strategy for the events brand ‘Blueprint’. - Male, Connor (2017)
The main purpose of this project is to develop a marketing plan for the events company ‘Blueprint’, on the basis of the findings from relevant resources and appropriate research. The study used a range of qualitative and quantitative methods in order to build enough data to construct an eight-point plan for the company’s management. We would hope that this plan is then incorporated into the firm’s future operations and used effectively to develop the company. The findings from this paper offer extensive opportunity for further research and provide a strong platform for any marketing practitioner who is commissioned to undertake further work for the company’s future development.